The Effect of Porang Flour (Amorphophallus Muelleri) as A Fat Replacer on the Acceptability and Characteristics of Cookies - Rindam Latief; Muhammad Asfar; Muthia Chairany; Musfirah Djalal (Jurnal Penelitian Pendidikan IPA, 2023)
Porang (Amorphophallus muelleri) is a tuber plant that contains a lot of glucomannan fiber. Glucomannan is a soluble fiber that can form a gel that mimics the characteristics of fat so that it has the potential to be used as a fat replacer in high-fat products such as cookies. The purpose of this study was to determine the effect of using fat replacer on the sensory acceptability and characteristics of cookies. The steps carried out in this study were to determine the concentration of porang flour in fat replacer (5 and 7.5%). Fat replacer with firmness that is closest to margarine at a concentration of 5%. Furthermore, cookies were made with fat replacer substitution (25, 50, and 75%). The cookies were then tested for their organoleptic properties using the hedonic method on the parameters of color, aroma, taste and texture. The best cookie formulation was obtained at 25% substitution, which was then compared with the control formulation by testing the parameters of proximate, crude fiber, texture, and oxalate content. The results showed that cookies with fat replacer had lower levels of ash, fat, protein, calories, and hardness than the control, although the difference in fiber and protein content was not significant.